AKIBAT HUKUM PERJANJIAN UTANG PIUTANG DENGAN PERALIHAN HAK ATAS TANAH SEBAGAI PELUNASAN UTANG DEBITUR WANPRESTASI - Yudi Syahputra; Ismawati Septiningsih; Itok Dwi Kurniawan (RESEARCH FAIR UNISRI, 2023)
This legal research aims to examine the legal consequences of debt agreements with the transfer of land rights as repayment of default debtors. This research is a normative legal research with a prescriptive and applied nature. The approach used in this research is a case study. The legal materials used are primary legal materials and secondary legal materials. The legal material collection technique used is library research. The legal material analysis technique used is the syllogism method. The results of this study indicate that collateral for debts in the form of land may not be transferred in the event of default, this is because it conflicts with Supreme Court Jurisprudence No. 2877 K/Pdt/1996, Law on Mortgage and Basic Agrarian Law. Therefore, debt agreements that make collateral as debt repayment by transferring rights in the event of default are null and void.